THE ROLE OF SOCIAL NETWORKS IN SHAPING HUMAN BEHAVIOUR - Asmita Debbarma (RADJA PUBLIKA, 2024)
The paper delves into the multifaceted influence of social networks on human behaviour, encompassing traditional and digital platforms. It explores the psychological dynamics within these networks, detailing the impact of social validation, peer pressure, and conformity on individual behaviour and identity projection. The evolution from traditional interpersonal connections to the digital revolution of social media platforms is analysed, highlighting their societal implications, including cultural, political, and economic influences. Challenges such as misinformation, privacy concerns, and mental health implications are discussed alongside suggestions for responsible usage, emphasizing digital literacy, diverse content consumption, and enhanced regulation. The paper concludes by envisioning future trends, focusing on emerging technologies, personalization, and ethical considerations crucial for the responsible evolution of social networking platforms.